Epidemiology, Classification and Treatment of Femur and Tibia Fractures around Total Knee Arthroplasty (Literature Review) - Zazirnyi, I.M. (TERRA ORTHOPAEDICA, 2024)
Summary. Periprosthetic fractures around total knee arthroplasty (TKA) are difficult to treat due to complex fracture morphology, high proportions of injuries associated with osteopenia, and the variability of injury patterns. Periprosthetic fractures associated with TKA are defined as fractures around the knee joint (femur, tibia, or patella) occurring within 5 cm of the intramedullary stem of the prosthesis or 15 cm of the joint. The incidence is estimated to be between 0.3% and 2.5% after primary TKA and up to 28% after revision TKA. There are several surgical and nonsurgical risk factors associated with postoperative periprosthetic fractures. Distal femoral periprosthetic fractures following TKA are the most common and reported to occur in 0.2–1.8% of patients after primary TKA. Tibial periprosthetic fractures have a reported prevalence of 0.07–0.1% in primary and 0.36% in revision knee arthroplasties. Patella fractures are the second most common periprosthetic fractures following TKA, with prevalence ranging from 0.68% to 1.19%, and are usually associated with a resurfaced patella. Several classification systems of periprosthetic fractures around TKA have been published and some treatment recommendations have been provided. However, most systems are subject to criticism and use different classification systems for the tibia, patella, and the femur.A variety of treatment methods are available for periprosthetic fractures. Conservative treatment can include protected weight bearing, splinting, or traction. Surgical treatment commonly involves closed intramedullary nailing or open reduction and internal fixation by plates. In cases of significant bone loss, a revision TKA may be indicated. In general, treatment must be guided based on the stability of the implant and the remaining bone quality, as determined by the presence of osteolysis and the location of the fracture.